2010
DOI: 10.1007/s10641-010-9640-y
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal of yellow phase Japanese eels Anguilla japonica after recruitment in the Kojima Bay-Asahi River system, Japan

Abstract: The density, size and age distribution were investigated for 233 eels, Anguilla japonica, sampled in fresh and brackish water areas of the Kojima BayAsahi River system, Okayama, Japan, to evaluate the possible patterns of dispersal of eels that recruit to this area. Migratory histories of 183 eels were categorized into 5 types depending on the Sr and Ca concentrations in their otoliths: (1) brackish water residents (74 fish, 40.4%), which settled in saline water and remained until capture; (2) freshwater resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 38 publications
(52 reference statements)
4
56
0
Order By: Relevance
“…For another temperate species, Japanese eel Anguilla japonica, a similar tendency has been reported, even though the differences shown in the studies were not statistically significant or were limited to a certain growth stage (Kotake et al 2005;Yokouchi et al 2008). However, a recent study has indicated the likelihood that Japanese eels have faster growth in saline water than in fresh water within the Kojima Bay-Asahi River system, where this study was conducted (Kaifu et al 2010). Faster growth enhances many fitness-related aspects of fishes, including a shorter amount of time to reach the adult stage and reproductive maturation and a decreased risk of predation (Hutchings 2006;Edeline 2007).…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…For another temperate species, Japanese eel Anguilla japonica, a similar tendency has been reported, even though the differences shown in the studies were not statistically significant or were limited to a certain growth stage (Kotake et al 2005;Yokouchi et al 2008). However, a recent study has indicated the likelihood that Japanese eels have faster growth in saline water than in fresh water within the Kojima Bay-Asahi River system, where this study was conducted (Kaifu et al 2010). Faster growth enhances many fitness-related aspects of fishes, including a shorter amount of time to reach the adult stage and reproductive maturation and a decreased risk of predation (Hutchings 2006;Edeline 2007).…”
Section: Introductionsupporting
confidence: 71%
“…Anguillid species use both fresh and saline water habitats in their growth phase. A considerable number of studies found consistent divergences of life history patterns in five species of temperate eels that include river, estuarine and marine residents, and multihabitat users that move from one habitat to another once or more during their growth phase (Jessop et al 2002;Tzeng et al 2002;Arai et al 2003;Daverat et al 2005;Kotake et al 2005;Daverat & Tomas 2006;Shiao et al 2006;Kaifu et al 2010). A considerable number of studies found consistent divergences of life history patterns in five species of temperate eels that include river, estuarine and marine residents, and multihabitat users that move from one habitat to another once or more during their growth phase (Jessop et al 2002;Tzeng et al 2002;Arai et al 2003;Daverat et al 2005;Kotake et al 2005;Daverat & Tomas 2006;Shiao et al 2006;Kaifu et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Most glass eels enter fresh water, migrating to the upper limits of tidal flow which in the old, flat continents occupied by A. anguilla and A. rostrata represents exclusively fresh water but for A. japonica can be either fresh or brackish water as mountains and the ocean stand adjacent to one another (Kaifu et al, 2010). Once freshwater is detected, this can trigger a range of behaviours: individuals either continue up-river, return to brackish water, or adopt a nomadic life-history where they use a range of saline habitats (Daverat et al, 2006;Cairns et al, 2009).…”
Section: Importance Of Saline Water Populationsmentioning
confidence: 99%
“…In addition, some eels change habitats during their growth phase (e.g. Tsukamoto et al 1998, Tsukamoto & Arai 2001, Jessop et al 2004, Daverat & Tomas 2006, Kaifu et al 2010, Yokouchi et al 2012. Studies on growth of anguillid eels showed that eels living in brackish habitats had a higher growth rate than eels living in freshwater habitats (e.g.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%